There is no intraocular affection on a SARS-CoV-2 - Infected ocular surface - Peer Lauermann; Marcus Storch; Michael Weig; Björn Tampe; Martin Winkler; Hans Hoerauf; Nicolas Feltgen; Samy Hakroush (American Journal of Ophthalmology Case Reports, 2020)
Purpose: The presence of SARS-CoV-2 RNA in anterior chamber fluid and/or the vitreous in patients with SARS-CoV-2 RNA on the ocular surface is unclear. Knowledge about the infectious state of intraocular structures could influence the daily work of ophthalmic surgeons. Observations: We analyzed ocular samples from a patient who had succumbed to COVID-19 pneumonia for the prevalence of SARS-CoV-2 RNA. We detected viral RNA in the ocular-surface samples on one swab and in one excidate from the conjunctiva. Samples from the anterior chamber and vitreous revealed no SARS-CoV-2 RNA. Conclusions: SARS-CoV-2 can effectively be inactivated with standard disinfection agents. The now proven absence of SARS-CoV-2 in intraocular fluids could influence how ophthalmic surgeons work. Without having to account for the risk of a contagion via the anterior chamber and/or vitreous body, the surgical staff would require no additional, more elaborate protection.